Surveillance of Anomalous Displacements in Large Buildings Through the Internet of Things: What Can Teach us the Surfside-Miami Events? - Nieto-Chaupis, Huber (2022)
The recent incidents at Surfside, Miami FL, can be seen as an inherent manifestation of modern structures whose risk were not anticipated in all, so that the periodical assessment of ground layers of particularly very large buildings might be a must henceforth by following local regulations done by specialized analyzers to calculate in a quantitative manner the deformation of structures as well as their exact ageing. In this paper, the idea of the implementation of a dedicated internet of things network to be called Internet of Tall Buildings (ITB in short) that should be running in an unstoppable manner for the sensing of geometrical deviations either at the top or bottom is presented. Thus, geometrical scenarios are proposed in order to measure the growth of angular displacements. A computational algorithm was designed in order to provide a solid idea of the potential advantage of ITB that might be realizable after the events of Surfside-Miami. The algorithm targets to calculate the angular deviations and how it is increasing in time. Once the allowed values are either reached or surpassed then the algorithm triggers all possible alarms that would give enough time to people to make fast decisions as well as to optimize their self-protection actions.